Предмет: Математика, автор: malchik1231

х-2     4х-1
----- = -------
х+3    4х+1

Ответы

Автор ответа: nadegakorf
0
(х-2)(4х+1)=(х+3)(4х-1)
4х2+х-8х-2=4х2-х+12х-3
4х2+х-8х-4х2+х-12Х=-3+2
-18х=-1
х=1/18
Вроде так!!!!!!!!!!!!!!)))))))))

Автор ответа: malchik1231
0
но всеравно спс
Автор ответа: nadegakorf
0
А как чувак??????????
Автор ответа: nadegakorf
0
Подскажи на будущее!!!!!!!!!!!!!!
Автор ответа: nadegakorf
0
ну че????????????
Автор ответа: nadegakorf
0
Спасибо!!!!!!!!!!!!!!!((((((((((((((((((
Похожие вопросы